Religious Involvement, Interpersonal Forgiveness and Mental Health and Well-Being Among a Multinational Sample of Muslims - AYTEN, ALİ (SPRINGER, 2020)
This study tested the links between religious involvement (assessed by religious beliefs and religious practices) and life satisfaction and generalized anxiety, and whether these links are mediated by interpersonal forgiveness. It utilized a sample of 706 university students recruited in three Muslim countries: Israel/Palestine, Turkey and Malaysia, and applied a cross-sectional methodology. Participants provided demographic information, and completed measures of religious beliefs, religious practices, interpersonal forgiveness (which is composed of three factors: hopefulness, avoidance, vengeance), life satisfaction and generalized anxiety. The findings indicated a positive link between religious practices and life satisfaction and a negative link between religious practices and generalized anxiety. Religious beliefs were positively tied to life satisfaction and unrelated to generalized anxiety. The hopefulness and avoidance factors of interpersonal forgiveness partially mediated the links between religious practices and life satisfaction, and the avoidance factor partially mediated the link between religious practices and generalized anxiety. On the other hand, none of the interpersonal forgiveness factors mediated the links between religious beliefs and both outcome measures. The findings suggest that religious practices have stronger connections with the health and well-being of Muslims, and that interpersonal forgiveness is one explanatory mechanism through which religious involvement is linked to health and well-being among this religious group.
Keywords: Religious involvement; Interpersonal forgiveness; Life satisfaction; Generalized anxiety; Muslims; ANXIETY DISORDER; PSYCHOTHERAPY; PERSONALITY; LIFE; SPIRITUALITY; CONSEQUENCES; ANTECEDENTS; RELIABILITY; DEPRESSION; MEDIATOR